Effects of 17α-methyltestosterone and letrozole on growth and gonadal development in largemouth bass (Micropterus salmodies) - Zhang, Dongyun; Li, Shengjie; Tian, Taihang; Du, Jinxing; Lei, Caixia; Zhu, Tao; Han, Linqiang; Song, Hongmei (Frontiers in Physiology, 2024)
In order to optimize the parameters for reversing masculinization and establish the techniques for sex induction of pseudo-males and creation of all-female fry in largemouth bass (Micropterus salmodies, LMB), 15-day-old LMB (1.00±0.10cm in length, 0.10±0.01g in weight) were fed a diet supplemented with either 17α-methyltestosterone (MT) or letrozole (LE) and their combination.The experimental groups were M20 (20mg/kg MT), L20 (20mg/kg LE) and M10L10 (10mg/kg MT and 10mg/kg LE). The control group, named C, was not feed MT or LE. After 60 days, exogenous hormone in the diets was stopped and the effects of MT and LE on growth, male ratio, and gonadal development in LMB were evaluated. At 12-month-old, blood and gonadal tissue samples were collected to measure sex steroid hormones levels, analyze expression levels of dmrt1 and cyp19a1a genes, as well as examine the gonads morphology. The results showed no significant differences in growth between the experimental groups and the control group after a 60-day feeding period with the formulated diet (P>0.05). The sex reversal ratio of M20, L20, M10L10 were 95.00%, 80.00%, 76.47%, respectively. The gonadal tissue sections showed that the gonadal structure of masculinized fish morphologic resembled that of control male fish. At 12-month-old, the sex reversal ratio in M20, L20, M10L10 and C groups were 100%, 86.67%, 73.33%, respectively. The testicular of pseudo-male fish in the M20 group exhibited well-developed morphology similarities to that of the control group males. However, the testes of pseudo-male fish in the L20 and M10L10 groups were smaller size Estradiol (E 2 ) levels in the experimental groups was significantly lower than those in the control group females (P<0.05), while testosterone (T) levels were significantly higher than that of the control group (P<0.05). Compared to the female fish in the control group, pseudo-male fish from all experimental groups showed significantly up-regulated expression of dmrt1 (P<0.05), and significantly down-regulated expression of cyp19a1a (P<0.05). Pseudo-males selected from group M20 exhibited a significantly higher proportion of female offspring (92.00%) compared to the control group (46.50%). In summary, 20mg/kg MT was the optimal inducing concentration.